Modeling the stress-strain state of variable-thickness composite shells and plates - Dimitrienko, Yu; Zakharova, Yu (E3S web of conferences, 2023)
A model for calculating the stress-strain state of variablethickness composite shells has been developed, based on assumptions such us the classical theory of Timoshenko-Mindlin shells. In the proposed model, the plate thickness is given by a function of curvilinear coordinates and is directly considered in the derivation of the equilibrium equations of the plate. The general equations of the theory of variable-thickness composite plates are derived. The article analyses the solution of the problem of plates bending under uniform pressure considering the variable thickness. For the numerical solution, the finite difference method (FDM) has been applied to the system of differential equations with matrix coefficients. For the resultant algebraic system, the FDM uses the tridiagonal matrix algorithm in computing the solution. The calculation results are compared with a plate of constant thickness. It is shown that the effect of thickness variability is quite significant.